21st century literature from the Philippines and the world - Uychoco, Marikit Tara A. (Sampaloc, Manila : Rex Book Store, Inc., 2016)
21st Century Literature from the Philippines and the World explores the literatures of the 21st century. It is divided into two parts: 21st Century Philippine Literature and 21st Century World Literature. It helps bridge the students' knowledge on formalist literary perspectives toward more post-colonial, socio-political perspectives about literature and society. Although the texts included have been published from 2000 and beyond, these span concerns about the new and the old. This book aims to help students understand the complex world they live in through the use of literature."
Includes references and index.
English text.